Formation Of General Competences in Students Of Higher Education Institutions - Toshpulatova Aziza Toyirovna (Euro Asian Journal Publishing, 2024)
The article provides information on improving general cultural competencies of students. Also, theoretical information is given and conclusions are drawn that competence is a necessary skill.
Keywords: education; knowledge; qualification; student